The Nature of God: God is Self-Existent, Omniscient, Sovereign, and Triune - Potana, Venkateswara Rao (International Journal of Scientific Research and Management (IJSRM), 2024)
It can be difficult for us to understand some aspects of God's nature since they are so different from what we normally experience as humans. We might eventually accept that these things are true of God as our trust in the Lord deepens, but we'll undoubtedly spend a lot of time pondering how these things function in the meantime. Due to their limited brains, humans find it difficult to understand God's nature, although it is clear from the scriptures that God has made himself known to be self-existent, omniscient, Sovereign, and Triune. Therefore, this paper attempts to understand the Biblical concept of the nature of God.